2004
DOI: 10.1086/379659
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Far‐Infrared Observations and Models of the Star Formation Core of G34.3+0.2C

Abstract: High spatial resolution far-infrared (FIR) maps made on the Kuiper Airborne Observatory are presented of the extremely bright source associated with the ''cometary'' ultracompact H ii region G34.3+0.2C. The maps show sharply peaked emission at G34.3+0.2C, surrounded by extended emission of uniform temperature. Maximum entropy method deconvolutions indicate FIR core source sizes of 12 00 and 20 00 at 47 and 95 m, respectively. Radiative transfer models of centrally heated dust cloud cores are presented that mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…It contains a group of UC H ii regions (G34.3+0.2 A, B, C; Campbell et al 2004) Six more masers associated with N67bis, N70, N71, N75, N79, and N91 were detected by Pandian et al (2007). This unbiased survey, carried out using the Arecibo radio telescope, is complete at the level of 0.27 Jy over the region l = 35.2 • to 53.7 • , |b| ≤ 0.41 • .…”
Section: Other Signposts Of Massive-star Formationmentioning
confidence: 99%
“…It contains a group of UC H ii regions (G34.3+0.2 A, B, C; Campbell et al 2004) Six more masers associated with N67bis, N70, N71, N75, N79, and N91 were detected by Pandian et al (2007). This unbiased survey, carried out using the Arecibo radio telescope, is complete at the level of 0.27 Jy over the region l = 35.2 • to 53.7 • , |b| ≤ 0.41 • .…”
Section: Other Signposts Of Massive-star Formationmentioning
confidence: 99%
“…The cometary G34.26+0.15C is not only associated with a hot molecular core (Hunter et al 1998;Campbell et al 2004;Mookerjea et al 2007), but also has an infall motion (Liu et al 2013) indicating that UC H II complex G34.26+0.15 is an ongoing massive star formation region. Additionally, several infrared bubbles are located in region III.…”
Section: Star Formation Scenariomentioning
confidence: 99%
“…This dust represents coagulated grains with ice mantles that would be expected to form from dust originally in the diffuse interstellar medium during the process of molecular cloud formation. It has been used to fit submm SEDs of high-mass protostellar cores (van der Tak et al 1999(van der Tak et al , 2000 and far-ir observations of the UC HII region G34.3+0.2 (Campbell et al 2004). However, when we examined its K(λ) behavior around 10 µm, we found that its silicate feature is shifted longward from 9.7 µm and broadened so that it does not appear to be compatible with our grism spectra.…”
Section: Overview Of a Simple Dust Continuum Modelmentioning
confidence: 99%
“…Deriving physical information from the continuum spectra is difficult because the actual geometry of the dust distribution is unknown, except that the sizes of the N band and 24.8 µm images limit the extent of the emitting structures. Experience with one-dimensional radiative transfer models of spectral energy distributions from UC HII regions (Campbell et al 1995(Campbell et al , 2000(Campbell et al , 2004, and inspection of the new spectra themselves suggest that there are ranges of temperatures in the emitting regions. However, the two-dimensional radiative transfer models of De Buizer et al (2005b) and Whitney et al (2003aWhitney et al ( ,b, 2004 show that orientation of flattened envelopes and outflow cavities dramatically affects the depth of the silicate absorption feature, as does emission and absorption by individual clumps in a clumpy dust cloud in the three-dimensional models of Indebetouw et al (2006).…”
Section: Introductionmentioning
confidence: 99%